Relationships between depression and difficulties in emotion regulation among first-year college students: a network analysis approach - Lingpei Liu; Ting Su; Jianyong Chen; Yingxiu Chen; Gu Liu (BMC Psychology)
Abstract Background Depression and difficulties in emotion regulation (DER) may co-occur in first-year college students due to the transition from high school to college environment. However, the intricate interaction dynamics between depression and difficulties in emotion regulation symptoms are unclear. This study employed network analysis to examine the network structure of depression and difficulties in emotion regulation among first-year college students. Methods This cross-sectional study included nine hundred and ninety-two first-year Chinese college students (M age = 18.68, SD = 0.85) who completed the Patient Health Questionnaire and Difficulties in Emotion Regulation Scale. Results “Lack of emotional clarity” and “non-acceptance of emotional responses” emerged as bridge symptoms for the network. The strongest connections are between “non-acceptance of emotional reactions” and “limited access to effective emotion regulation strategies”, “impulse control difficulties”, and “difficulties engaging in goal-directed behavior”, respectively. Network structure and global strength did not differ by gender, but some edge weights varied. Conclusion These findings can inform the development of interventions targeting comorbid depression-DER onset among transitioning college students.